Use of composite mesh in gastroschisis: A unique approach - Vishesh K Dikshit; Rahul K Gupta; Abhaya R Gupta; Paras R Kothari; Ravikiran S Kamble; Geeta A Kekre; Prashant S Patil (Wolters Kluwer Medknow Publications, 2015)
Gastroschisis is a congenital defect of the abdominal wall involving evisceration of abdominal contents. Initial surgical treatment of this condition depends on the size of the defect, size of the abdominal cavity and amount of bowel exposed. Various techniques described are primary closure, use of the skin flap and silo bag application, followed by fascial closure. Here we present a case wherein even after 7 days of silo bag application, fascial closure was not possible, and a composite mesh was used to cover the bowel until further repair could be attempted.